The role of Instagram in promoting mental health awareness and help-seeking attitudes among Malaysian university students - Idzreen Nur Fathennadwa Mohamad; Nur Nadia Abd Mubin; Ahmad Jazimin Jusoh (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the effect of Instagram (IG) usage for seeking mental health information and emotional support on help-seeking attitudes via mental health awareness among university students in Perak, Malaysia. Utilizing the Media Dependency Theory, a quantitative approach was adopted with data collected from 364 undergraduate students at Sultan Idris Education University (UPSI) and MARA University of Technology (UiTM) through a 44-item questionnaire. Descriptive analysis and Structural Equation Modelling were conducted to analyze the data. Findings indicated moderate IG usage for seeking mental health information and emotional support, high mental health awareness, and positive help-seeking attitudes. Specifically, IG usage for mental health information indirectly influenced help-seeking attitudes through mental health awareness, while seeking emotional support had a direct effect but was not mediated by mental health awareness. The study reveals that despite the predominant use of IG for entertainment, a significant portion of students also engaged with the platform for mental health-related purposes. This engagement contributes to their overall awareness of mental health issues and their willingness to seek help. The implications of these findings suggest that IG can be an effective platform for mental health promotion among university students. These findings suggest strategies for social media accounts promoting mental health to enhance engagement and spread awareness, particularly among Malaysian university students, to mitigate the stigma around help-seeking.